IDENTIFIKASI TINGKAT KEJUJURAN SISWA SEKOLAH DASAR MELALUI GEROBAK KEJUJURAN DI KOTA SEMARANG - Reffiane, Fine; Saputra, Henry Januar; Hidayat, Taufik (Mimbar Sekolah Dasar, 2015)
The background of this research is the importance of the school to know the student's honesty degree. Purpose of research implementation is to measure the elementary school student's honesty degree. The research did on Mei 2013 until Juny 2013 at Pendrikan Lor 02 State Elementery School Semarang City. This research used qualitative method. Data resources result from observations, interviews, and documents. Data analysis technique did triangular. The results showed that honesty of students in Pendrikan Lor 02 State Primary school Semarang City, not yet reached 100% fully. There are still some students who have not been able to behave honestly. Dishonest behavior is caused by (1) the opportunity; (2) environmental conditions (students come from poor environment and uneducated). Nevertheless, from the data graph shows that an increase in the level of honesty from day to day although it also occurs conditions showed that the level of honesty decreased.Keywords: honesty, cart, elementary school.